Vostok : istoriya i kultura : Professoru Yu. A. Petrosyanu k 70-letiyu so dnya rojdeniya = East : history and culture to Professor Yu. A. Petrosyan on the occasion of his 70th birthday (Sankt-Peterburg)
295 s.